Potensi Limbah Tulang Kambing Sebagai Arang Aktif Yang Teraktivasi Asam Sulfat - Sari Wardani; Elvrida Rosa (Jurnal Serambi Engineering, 2018)
Bone is one of the wastes result in environmental pollution and public health issues if it is thrown directly into the environment. The aim of this research was to study the characteristics of activated charcoal of activated sulfuric acid goat bone. The process of making activated charcoal of goat bone included two stages of process, herein consisted of first carbonization process of goat bone at temperature of 700  C for 20 minutes to produce goat bone charcoal. The second process is chemical activation by using sulfuric acid activator at various concentrations of 1N, 2N and 3N for24 hours. The results showed that the best activated charcoal characteristic of sulfuric acid was at 3N sulfuric acid concentration, 0.289% moisture content, ash content of 6.4%, absorption capacity of Iod 983 mg / g, volatile matter 15,017, fixed carbon 82.013 and spectra FTIR of activated carbon showed spectra of absorption band at wave number 3546,143 – 3604,135 cm-1 on vibration of group -OH, with intensity 76%. Overall, the results revealed that the quality of activated charcoal of goat bone isstill eligible of the values recommended by SNI-06-4253-1996 about the quality of activated charcoal.